Groundwork: Preparing an effective basis for communication and shared learning in design and technology education - Looijenga, Annemarie; Klapwijk, Remke; Vries, Marc J. de (Design and Technology Education: An International Journal, 2016)
In Dutch Design and Technology Education the beginning of a process of learning is usually determined by the teacher. In this paper it is argued that a beginning, determined in interaction with the students, is more profitable as the interaction will lead to joined-up exploring, creating and thinking and an increased motivation to learn. Furthermore, students are empowered to treat an activity as a means rather than an end. The interaction acts as groundwork in advance of the assignment. Groundwork is something that is done at an early stage and that makes later work or progress possible. Literature does however not cover the groundwork topic for children in the four-eight year age bracket. Therefore a model for the groundwork phase, consisting of five components, was designed and tested. The components are: context, communication, integration of acting and thinking, presentation of instruction and presentation of the problem. In this paper two case-studies, which handle groundwork in different ways, are described. The groundwork was in both cases addressed in group activities, aiming to prepare students to commence a process of learning. The cases show that, when used in combination, the five components appear to make groundwork successful. Careful communication gave added value. A communication link was configured between teacher and learner, between learners, and between subject and learner. Through groundwork the teacher shared both thoughts and knowledge with the students and this created a base for effective classroom communication and a common approach.